2022
DOI: 10.3390/nu14142992
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Gut Microbiota and Respiratory Tract Infections in Childhood: A Narrative Review

Abstract: Respiratory tract infections (RTIs) are common in childhood and represent one of the main causes of hospitalization in this population. In recent years, many studies have described the association between gut microbiota (GM) composition and RTIs in animal models. In particular, the “inter-talk” between GM and the immune system has recently been unveiled. However, the role of GM in human, and especially infantile, RTIs has not yet been fully established. In this narrative review we provide an up-to-date overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The resident microbiota, consisting of trillions of microbes and their derived metabolites in the GI tract, are critical regulators in modulating host immune defense against pathogen infections [ 20 ]. It has been shown that respiratory infections are associated with gut microbiota dysbiosis in children [ 21 ]. Enterococcus was increased, whereas the abundances of Eubacterium , Faecalibacterium , and Bifidobacterium were reduced in children with recurrent respiratory tract infections [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resident microbiota, consisting of trillions of microbes and their derived metabolites in the GI tract, are critical regulators in modulating host immune defense against pathogen infections [ 20 ]. It has been shown that respiratory infections are associated with gut microbiota dysbiosis in children [ 21 ]. Enterococcus was increased, whereas the abundances of Eubacterium , Faecalibacterium , and Bifidobacterium were reduced in children with recurrent respiratory tract infections [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization develops at surfaces such as the skin, lung, and mucosa of the aerodigestive tract, and the role of the microbiota in these locations has recently been the focus of much attention. The gut microbiome significantly affects the risks for asthma and allergies among genetically predisposed atopic individuals [ 31 ]. Prebiotic foods (e.g., dietary fiber, fruits, vegetables, and resistant starch) and probiotic foods (e.g., yogurt, kefir, kimchi, miso, pickles, sauerkraut, and tempeh) promote the growth and maintenance of Bifidobacterium species, some Clostridia species , and Lactobacilli [ 32 ].…”
Section: Allergies Asthma and The Microbiomementioning
confidence: 99%
“…However, caution is advised in interpreting these findings, as subgroup analyses highlighted the need for further research in this area (Scott et al 2019). Dysbiosis, characterized by disruptions in gut microbiota composition and diversity, has been linked to immune dysregulation, potentially rendering individuals more susceptible to infections, including ear infections (Ihekweazu and Versalovic 2018;Willers and Viemann 2021;Zama et al 2022).…”
Section: Introductionmentioning
confidence: 99%